Adult Outcomes After Newborn Respiratory Failure Treated With Extracorporeal Membrane Oxygenation*. Issue 1 (January 2017) - Engle, William A.; West, Karen W.; Hocutt, Gail A.; Pallotto, Eugenia K.; Haney, Barbara; Keith, Rachel J.; Stewart, Dan L.; Knodel, Ellen; Suttner, Denise; Chapman, Rachel; Thomas, Alison; Schwerin, Beverly; et al.
Abstract : Objective: To describe the outcome of young adults treated for hypoxemic respiratory failure with extracorporeal membrane oxygenation as neonates. Design: The study was designed as a multisite, cross sectional survey. Setting: The survey was completed electronically or on paper by subjects and stored in a secure data base. Subjects: Subjects were surviving neonatal extracorporeal membrane oxygenation patients from eight institutions who were18 years old or older. Interventions: None. Measurements and Main Results: A questionnaire modified from the 2011 Behavioral Risk Factor Surveillance System and the 2011 National Health Interview Survey with additional unique questions was completed by subjects. Results were compared to age-matched national Behavioral Risk Factor Surveillance System and National Health Interview Survey data. One hundred and forty-six subjects participated (8.9% of eligible candidates). The age at questionnaire submission was 23.7 ± 2.89 years. Subjects differed statistically from national cohorts by being more satisfied with life (93% vs 84.2%); more educated (some college or degree; 80.1% vs 57.7%); more insured for healthcare (89.7% vs 72.3%); less frequent users of healthcare in the last 12 months (47.3% vs 58.2%); more limited because of physical, mental, and developmental problems (19.9% vs 10.9%); and having more medical complications. Furthermore, learning problems occurred in 29.5% of the study cohort. The congenital diaphragmatic hernia group was generally less healthy and less well educated, but equally satisfied with life. Perinatal variables contributed little to outcome prediction. Conclusions: Most young adult survivors in this study cohort treated with extracorporeal membrane oxygenation as neonates are satisfied with their lives, working and/or in college, in good health and having families. These successes are occurring despite obstacles involving health issues such as asthma, attention deficit disorder, learning difficulties, and vision and hearing problems; this is especially evident in the congenital diaphragmatic hernia cohort. Selection bias inherent in such a long-term study may limit generalizability, and it is imperative to note that our sample may not be representative of the whole. Abstract : Supplemental Digital Content is available in the text.